The Role of the “Informational Turn” While Shaping a Modern IT Personality’s Scientific Worldview - Olga Korchazhkina (Современные информационные технологии и IT-образование)
The article deals with the scientific and methodological phenomenon caused by the birth of the Theory of Information, which made it possible to carry out a quantitative analysis of both information sources and the entropy as a measure of information uncertainty. A new scientific trend, which originated in the middle of the XXth century, gave the beginning of a philosophical movement that united a set of disciplines, such as Psychology, Computer Science, Cybernetics, and Philosophy, and was called the “cognitive revolution”, or the “information turn” as well. From the “informational turn” standpoint which influenced the change of the philosophical paradigm in the development of Cybernetics, information received the status of the basis on which the human brain is built. Cybernetics, which was the first to claim the title of New science, began to be understood as a new interpretation of Man and human knowledge about the Universe and Society, combining the study of communication strategies, management and self-regulation, as well as ways of interaction between Homo sapiens and the machine with a built-in expedient behaviour. Over the years, as the transition to the new realities of the post-non-classical period in the development of science and technology, Synergetics was the discipline that also began to aspire to the title of New Science. Nevertheless, Cybernetics, Information Theory and Computer Science as sources of the most powerful tools for working with information resources, organizing educational and professional activities and as fundamental disciplines in shaping the modern picture of the world, will not exhaust their potential for a long time. Such prospects, expanding the possibility of managing cognitive processes, led to the need to strengthen the humanitarian component in educational programmes for IT specialties, ensure a change in methodology and develop fundamentally different approaches to teaching engineering and technical disciplines. In addition, the new content of the sciences that caused the birth of the “information turn” as well as strengthening of worldview aspects in the perception of knowledge about the Universe and Society were contributed by the philosophical paradigm of complexity, the basis of which was an updated theory of knowledge, built on scientific principles of an explanatory, rather than on predictive nature.